1998 ISEK Congress Keynote Lecture: Multi-muscle control in human movements - G. Feldman, Anatol; F. Levin, Mindy; Mitnitski, Arnold M; Philippe Archambault (Journal of electromyography and kinesiology, 1998)
It has been suggested that the coordination of the activity of multiple muscles results from the comparison of the actual configuration of the body with a referent configuration specified by the nervous system so that the recruitment and gradation of the activity of each skeletal muscle depend on the difference between these two configurations. Active movements may be produced by the modification of the referent configuration. The hypothesis predicts the existence of a global minimum in electromyographic (EMG) activity of multiple muscles during movements involving reversals in direction. This prediction was tested in five subjects by analysing movements resembling the act of reaching for an object placed beyond one's reach from a sitting position. In such movements, initially sitting subjects raise their body to a semi-standing position and then return to sitting. Consistent with the hypothesis is the observation of a global minimum in the surface EMG activity of 16 muscles of the arm, trunk and leg at a specific phase of the movement. When the minimum occurred, EMG activity of each muscle did not exceed 2–7% of its maximal activity during the movement. As predicted, global EMG minima occurred at the phase corresponding to the reversal in movement direction, that is, during the transition from raising to lowering of the body. The global EMG minimum may represent the point at which temporal matching occurs between the actual and the referent body configurations. This study implies a specific link between motor behavior and the geometric shape of the body modified by the brain according to the desired action.